Tissue Expanders in Staged Calvarial Reconstruction: A Systematic Review - Lo, Andrea Y.; Yu, Roy P.; Raghuram, Anjali C.; Cooper, Michael N.; Thompson, Holly J.; Liu, Charles Y.; Wong, Alex K. (Archives of Plastic Surgery, 2022)
Cranioplasties are common procedures in plastic surgery. The use of tissue expansion (TE) in staged cranioplasties is less common. We present two cases of cranioplasties with TE and systematically review literature describing the use of TE in staged cranioplasties and postoperative outcomes. A systematic review was performed by querying multiple databases. Eligible articles include published case series, retrospective reviews, and systematic reviews that described use of TE for staged bony cranioplasty. Data regarding study size, patient demographics, preoperative characteristics, staged procedure characteristics, and postoperative outcomes were collected. Of 755 identified publications, 26 met inclusion criteria. 85 patients underwent a staged cranioplasty with TE. Average defect size was 122 cm2, and 30.9% of patients received a previous reconstruction. Average expansion period was 14.2 weeks. The most common soft tissue closures were performed with skin expansion only (75.3%), free/pedicled flap (20.1%), and skin graft (4.7%). The mean postoperative follow-up time was 23.9 months. Overall infection and local complication rates were 3.53 and 9.41%, respectively. The most common complications were cerebrospinal fluid leak (7.1%), hematoma (7.1%), implant exposure (3.5%), and infection (3.5%). Factors associated with higher complication rates include the following: use of alloplastic calvarial implants and defects of congenital etiology (p = 0.023 and 0.035, respectively). This is the first comprehensive review to describe current practices and outcomes in staged cranioplasty with TE. Adequate soft tissue coverage contributes to successful cranioplasties and TE can play a safe and effective role in selected cases.
Keywords: plastic surgery; cranioplasty; tissue expander; calvarium